2000
DOI: 10.1161/01.atv.20.11.2408
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein Concentrations During Treatment and Recurrent Coronary Artery Disease Events

Abstract: Abstract-The effect of untreated total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) as cardiovascular risk factors in both primary and secondary prevention has been extensively investigated. The predictive value of on-treatment lipid and apolipoprotein levels on subsequent cardiovascular events is as yet uncertain. Eight hundred forty-eight patients (675 men and 173 women) with angiographically proven coronary artery disease (CAD) who received effective statin therapy (Ն30% decrease of base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
81
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 44 publications
(29 reference statements)
4
81
0
4
Order By: Relevance
“…5 Numerous studies have identified HDL cholesterol and its major protein component, apolipoprotein A-I (apoA-I), as having a direct protective role against the development of CAD. 5,6 There has been tremendous interest in the effect of HMG-CoA reductase inhibitors on HDL metabolism, with reports that the various agents in this class appear to have quantitatively different effects on HDL levels. 3,7,8 Atorvastatin, in contrast to some other statins, appears to lose its HDL-raising effect at higher drug doses.…”
mentioning
confidence: 99%
“…5 Numerous studies have identified HDL cholesterol and its major protein component, apolipoprotein A-I (apoA-I), as having a direct protective role against the development of CAD. 5,6 There has been tremendous interest in the effect of HMG-CoA reductase inhibitors on HDL metabolism, with reports that the various agents in this class appear to have quantitatively different effects on HDL levels. 3,7,8 Atorvastatin, in contrast to some other statins, appears to lose its HDL-raising effect at higher drug doses.…”
mentioning
confidence: 99%
“…As partículas aterogênicas de LDL e os remanescentes de quilomícrons e lipoproteína de muito baixa densidade (VLDL) apresentam uma molécula de ApoB como parte da estrutura protéica. Por isso, a concentração plasmática de ApoB tem sido considerada um melhor representante das partículas aterogênicas ou do colesterol não-HDL, e alguns estudos têm demonstrado que níveis plasmáticos elevados de ApoB podem ser um valioso preditor de DAC (26) .…”
Section: Discussionunclassified
“…Rupture of atherosclerotic plaques and formation of thrombi are the primary mechanisms of myocardial infarction or cerebrovascular accidents. Atherosclerosis is therefore a dynamic inflammatory disorder and the biological composition and inflammatory state of an atherosclerotic plaque, rather than the degree of stenosis or its size, are the major determinants of acute clinical events [1,2]. Noninvasive techniques to detect vulnerable atherosclerotic plaque are critically needed.…”
mentioning
confidence: 99%